Pendekatan rangkaian neural bagi sistem pengecaman tandatangan tulisan tangan - Siraj, Fadzilah; Wan Ishak, Wan Hussain; Mat Yatim, Fadzilah (Fakulti Sains Komputer dan Sistem Maklumat, Universiti Teknologi Malaysia, 2001)
Internet has been used as a medium for electronic transaction.Electronic security system such as digital signature has been used to control on-line transaction. Digital signature is a string of bit that represents another string of bit.However, due to security concerns such as human error, storage and code breaking, it is vital to explore a new technology to enhance security for on-line transaction.This paper discusses neural networks model for on-line handwritten signature verification.Several neural networks model have been identified and tested to choose the suitable neural network model for on-line handwritten signature verification.